1997
DOI: 10.2105/ajph.87.9.1499
|View full text |Cite
|
Sign up to set email alerts
|

Social differences in health: life-cycle effects between ages 23 and 33 in the 1958 British birth cohort.

Abstract: OBJECTIVES: The purpose of this study was to determine whether social differences in health persist or widen during early adulthood. METHODS: A longitudinal follow-up of the 1958 British birth cohort was investigated, using social class at birth and six health measures at ages 23 and 33. A slope of inequality was estimated to represent social differences in health. RESULTS: Social gradients in health were evident by age 23: the prevalence of poor health increased with decreasing social position. This was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
39
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 32 publications
5
39
0
Order By: Relevance
“…[13][14][15][16][17] Social inequalities in self-rated health are also well documented; people from lower social classes rate their health poorer compared to those from higher social classes. [18][19][20][21] In terms of gender differences in social inequalities of self-rated health, several previously conducted studies have shown that the magnitudes of social class inequalities in self-rated health differ between males and females, with shallower or more inconsistent gradients found among females than males. [20][21][22] However, some studies show that males and females have a similar pattern of social inequality in self-rated health.…”
Section: Survey Populations and Study Samplementioning
confidence: 99%
“…[13][14][15][16][17] Social inequalities in self-rated health are also well documented; people from lower social classes rate their health poorer compared to those from higher social classes. [18][19][20][21] In terms of gender differences in social inequalities of self-rated health, several previously conducted studies have shown that the magnitudes of social class inequalities in self-rated health differ between males and females, with shallower or more inconsistent gradients found among females than males. [20][21][22] However, some studies show that males and females have a similar pattern of social inequality in self-rated health.…”
Section: Survey Populations and Study Samplementioning
confidence: 99%
“…A considerable body of empirical literature also indicates that the associations between SES and health outcomes can vary with both the socioeconomic measure and the health indicator being examined. [9][10][11][12][13][14] Parker et al used data from the nationally representative 1988 National Maternal and Infant Health Survey to look at SES measures in relation to three maternal and child health outcomes: low birthweight, small-for-gestational-age, and preterm birth. 14 They found that among both "black" and "white" postpartum women, family poverty status, maternal education, paternal education, maternal occupation, and paternal occupation were generally not highly correlated.…”
mentioning
confidence: 99%
“…The model starts with a cohort of children distributed by weight status per the UK90 growth reference standards 51 using clinical assessment classifications (≤ 91st centile; > 91st to ≤ 95th centile; > 95th to ≤ 98th centile; and > 98th centile), and predicts the expected distribution of the cohort by weight status in adulthood. Data from the UK longitudinal study reported by Power et al, 76 which followed up participants from age 7 to age 33 years [see detail in Model development (stage 1): predicting adult weight status from child weight status], are used to predict adult weight status. Based on data reported by Power et al,…”
Section: Model Structure (Summary)mentioning
confidence: 99%
“…A total of eight studies were identified. 75,76,[80][81][82][83][84][85] Of these, four 75,76,80,85 presented data projecting weight status from childhood into adulthood and included classifications by weight status (healthy weight, overweight), and were therefore selected for consideration to populate the model. The remaining four studies were excluded, either because they provided no usable data 81,82,84 or because the data were for a child age range that was inappropriate for the current research.…”
mentioning
confidence: 99%
See 1 more Smart Citation